The polarographic and corrosion inhibition performance of some Schiff base compounds derived from 2-amino-3-hydroxypyridine in aqueous media - M. Abdallah; M. Alfakeer; H.M. Altass; Ahmed M. Alharbi; Isamil Althagafi; N.F. Hasan; E.M. Mabrouk (Egyptian Journal of Petroleum)
The polarographic behavior of five Schiff bases compounds (SB) prepared from 2-amino-3-hydroxypyridine was investigated in BR buffer series of pH 2–12. The polarograms of all SB compounds displayed a single irreversible diffusion-controlled 2-electron wave within the whole pH range representing the saturation of the NCH bond. The effect of pH and substituents on electrode reaction have been investigated and discussed. The electrode reaction pathway is found to be H+, e, e, H+ in which the proton uptake precedes the electron transfer. The studied compounds were used as inhibitors for corrosion of carbon steel (CS) in 1 M HCl solution using potentiodynamic polarization technique. The inhibition was explained in view of the adsorption of SP compounds on the CS surface obeying to Freundlich isotherm. These compounds act as good inhibitors as the inhibition efficiency reached 89.5%. The inhibition efficiency of the studied SBs is found to be a function of substituent group. The order of inhibition efficiency follows the sequence: N(CH3) > p-OCH3 > o-OH > H > p-Cl. This order agrees with the sequence of the negative shift in E1/2 values of the SB compounds under investigation. Keywords: Pyridine Schiff bases, Polarography, Corrosion inhibitor, Adsorption